Pengaruh Produk dan Nilai Pelanggan terhadap Keputusan Pembelian Produk Air Mineral Galon Merek Aqua - Ahmad Darda; Ahmad Rojikun (Neolectura, 2022)
This study aims to determine the effect of product and customer value on purchasing decisions of Aqua brand gallon mineral water, either partially or simultaneously. Primary data were collected from the community in RT.03 RW.02 Kelurahan Pasir Putih, Sawangan District, Depok, West Java which has 105 families, because in this study it was a product of gallons of drinking water commonly used in families, so this study was the object of this research. The research is a representative of one family who is willing to be interviewed and fill out a questionnaire, determining the sample using the Slovin formula, so that only 85 respondents were selected. The collected data was processed using multiple linear regression analysis. From the results of data analysis using multiple linear regression, it can be concluded that the product and customer value partially have a significant effect on purchasing decisions. Furthermore, product and customer value together have a significant effect on purchasing decisions.